Maternal alcohol intake prior to and during pregnancy and risk of adverse birth outcomes: evidence from a British cohort. Issue 6 (10th March 2014) - Nykjaer, Camilla; Alwan, Nisreen A; Greenwood, Darren C; Simpson, Nigel A B; Hay, Alastair W M; White, Kay L M; Cade, Janet E
Abstract : Background: Evidence is conflicting regarding the relationship between low maternal alcohol consumption and birth outcomes. This paper aimed to investigate the association between alcohol intake before and during pregnancy with birth weight and gestational age and to examine the effect of timing of exposure. Methods: A prospective cohort in Leeds, UK, of 1303 pregnant women aged 18–45 years. Questionnaires assessed alcohol consumption before pregnancy and for the three trimesters separately. Categories of alcohol consumption were divided into ≤2 units/week and >2 units/week with a non-drinking category as referent. This was related to size at birth and preterm delivery, adjusting for confounders including salivary cotinine as a biomarker of smoking status. Results: Nearly two-thirds of women before pregnancy and over half in the first trimester reported alcohol intakes above the Department of Health (UK) guidelines of ≤2 units/week. Associations with birth outcomes were strongest for intakes >2 units/week before pregnancy and in trimesters 1 and 2 compared to non-drinkers. Even women adhering to the guidelines in the first trimester were at significantly higher risk of having babies with lower birth weight, lower birth centile and preterm birth compared to non-drinkers, after adjusting for confounders (p<0.05). Conclusions: We found the first trimester to be the period most sensitive to the effect of alcohol on the developing fetus. Women adhering to guidelines in this period were still at increased risk of adverse birth outcomes. Our findings suggest that women should be advised to abstain from alcohol when planning to conceive and throughout pregnancy.